Am I riskier if I rescue my banks? Beyond the effects of bailouts - Cuadros-Solas, Pedro J.; Salvador, Carlos; Suárez, Nuria (Journal of Financial Stability, 2021)
We examine the relationship between bank bailouts and sovereign risk in 35 countries and 19 bailouts from 2005 to 2015. Bailouts negatively affect sovereign ratings, with rating agencies consistently perceiving higher risk when a country’s banking system has been rescued (risk-increasing effect). The increase in public debt as a result of the bank bailouts is the main mechanism through which the risk-increasing effect occurs. Moreover, financial soundness and banking market structure shape the impact of bailouts on sovereign risk. In particular, proactiveness in undertaking public bailouts for banking systems that are largely distressed – that is, risky and low profitable – and highly concentrated seems to lead to smaller increases in sovereign risk. However, the strength of the connection between the public sector and the banking system neither moderates nor magnifies the impact of bailouts. Furthermore, rating dynamics (duration, momentum, and timing) reinforce the importance and duration of the effect of bailouts on sovereign ratings. The results are robust to endogeneity concerns, sample selection bias and several robustness tests.